Studying the Effect of Potato Cold Hardening on Integrity of Meristems, Cryopreserved by Slow Freezing - Shevchenko, Nadiya; Stribul, Tamara; Rozanov, Leonid (Probl Cryobiol Cryomed, 2006)
Cold hardening effect on potato meristem integrity at two-step cryopreservation has been studied. Such cryoprotectants as dimethyl sulfoxide (DMSO) and 1,2-propanediol (1,2-PD) have been used. Freezing of hardened potato apexes under DMSO protection was established to increase their integrity in comparison with the same index in non-hardened meristems. Potato apex hardening is inexpedient when using 1,2-PD. Observation for cryopreserved meristem development within 30 days has demonstrated that treatment with cryoprotectants and freezing inhibit an apex growth in comparison with the control. 1,2-PD occurred to be less toxic. DMSO treatment can cause callus-genesis.
Stribul TF, Shevchenko NA, Rozanov LF. Studying the Effect of Potato Cold Hardening on Integrity of Meristems, Cryopreserved by Slow Freezing. Prob Cryobiol Cryomed. 2006. 16(1): 60–65.
Keywords: meristem; cold hardening; cryoprotectant; cryopreservation; freezing